Fundamental Rights in the Eec Treaty and Within Community Freedoms - Konstantinos Margaritis (CES Working Papers, 2013)
It has been widely argued that the European Economic Community (EEC) was based on principles of economic integrity and growth through the creation of a common market; this is not far from reality. The Treaty of Rome was full of provisions that enhanced economic co-operation and increased the sense of liberalization in Europe, such as the four, now traditional, Community freedoms. Although all the above applied, there were articles within the EEC Treaty where fundamental rights were guaranteed; more than that, fundamental rights that occurred from the Community freedoms, even in a basic level. This is of highest importance since the interpretation of those provisions gave the initiative for further development in the field of fundamental rights protection within the Community legal order, throughout legislative procedure and case law. The aim of this paper is to present the fundamental rights as highlighted in the EEC Treaty and critically approach their concept under Community law.
Keywords: E61; F68; J83; K39; 330; Fundamental Rights; Economic Freedoms; EEC Treaty; ECJ case law Romania